Application of a Cardiac Septal Occluder in a Patient Affected by Enteroatmospheric Fistula - Basiricò Floriana; Galli Alessandro; Giudicissi Rosina; Fucini Claudio (Journal of Colon And Rectal Cancer, 2016)
Enteroatmospheric fistula is a challenging and emerging clinical situation, mainly related to “open abdomen” technique in damage control surgery for trauma and in case of multiple laparotomies. We report the case of a 61-year-old male patient, affected by rectal carcinoma, submitted to standard surgical treatment and gradually evolving in persistent proximal jejunal fistula. The positioning of a cardiac septal occluder (Amplatzer®) was associated with immediate and late favourable effects. The procedure was conducted “bed-side” and turned out to be easy and safe.
Keywords: cardiac septal occluder